Trends in antibiotic use before and during the coronavirus disease 2019 (COVID-19) pandemic across an integrated health system with different antimicrobial stewardship program models trends in antibiotic use by ASP model. Issue 1 (8th April 2022) - Peterson, Jennifer M.; White, Kristina; Muehling, Emily; Ebert, Steven C.; Lambi, Lisa; Thieman, Corey; Peterson, Nathan; Deuel, Kia; Bushman, Amanda M.; Kumar, Sudhir; Best, Leyla A.; Rosa, Rossana
Abstract: Changes in antimicrobial use during the pandemic in relation to long-term trends in utilization among different antimicrobial stewardship program models have not been fully characterized. We analyzed data from an integrated health system using joinpoint regression and found temporal fluctuations in prescribing as well as continuation of existing trends.